First light in the universe - Loeb, Abraham. (Springer, 2017)
Contains the worked out lectures given at the 36th Saas-Fee Advanced Course "First Light in the Universe" by three scientists in the field: Abraham Loeb, Andrea Ferrara, and Richard Ellis. This book provides a comprehensive introduction to the physics of galaxies, stars, the interstellar and intergalactic medium in the early Universe.